Single rRNA Helices Bind Independently to the Protein‐Conducting Channel SecYEG. (17th January 2013) - Behrens, Christina; Hartmann, Enno; Kalies, Kai‐Uwe
Abstract : Ribosomes tightly interact with protein‐conducting channels in the plasma membrane of bacteria (SecYEG) and in the endoplasmic reticulum of eukaryotes (Sec61 complex). This interaction is mediated by multiple junctions and is highly conserved during evolution. Although it is well known that both ribosomal proteins and ribosomal RNA (rRNA) are involved in the ribosome–channel interaction, detailed analyses on how these components contribute to this binding are lacking. Here, we demonstrate that the evolutionary conservation of ribosome binding is solely mediated by rRNA. Moreover, we show that in vitro transcribed 23 S rRNA binds with similar characteristics to protein translocation channels as native 23 S rRNA or 50 S ribosomal subunits. This indicates that base modifications, which exist in native rRNA, do not crucially influence the binding. In two of the ribosome‐channel junctions (c1 and c2), exclusively rRNA helices are involved. Using in vitro transcribed rRNA mutants, we now provide evidence that large parts of the rRNA can be deleted without altering its binding properties, as long as the rRNA helices of the c1 and c2 junctions remain intact. We demonstrate that the connection sites c1 and c2 generate high‐affinity binding sites that act independently of each other. This could explain why membrane‐bound ribosomes have an extremely low off‐rate .